Intravenous metastasis of unexpected uterine sarcoma in the context of uterine fibroids: case report and literature review - Huang, Wenying; Zhang, Tianwei; Wang, Hui; Liu, Zhengchun; Zhai, Peiling; Wang, Xinbo; Wang, Shuai (Frontiers in Oncology, 2024)
Objective: Endometrial stromal tumors are rare and complex mesenchymal tumors that often present with clinical symptoms similar to uterine leiomyomas. Due to their atypical nature, they are prone to be misdiagnosed or overlooked by healthcare professionals. This study presents a case report of an incidentally discovered endometrial stromal sarcoma with venous metastasis, which was initially misdiagnosed as a uterine leiomyoma. In addition, this study reviews previously documented cases of similar tumors.Case report: During a routine medical examination in 2016, a 50-year-old woman was diagnosed with uterine fibroids. In June 2020, she began experiencing moderate, irregular vaginal bleeding.Nevertheless, a histopathological examination indicated an endometrial stromal sarcoma with a striking amalgamation of both low-grade and high-grade features. Molecular analysis identified a rare MED12 gene mutation. The patient underwent total hysterectomy, bilateral salpingectomy, and resection of the metastatic lesions. Postoperative management included radiotherapy, chemotherapy, and hormone therapy. After completion of chemotherapy, the patient was followed up for 27 months with no evidence of tumor recurrence. Conclusion: This case report highlights the importance of pathological, immunohistochemical, and molecular aspects of this rare tumor involving the inferior vena cava and showing the presence of atypical gene mutations. The successful treatment outcome further emphasizes the importance of advances in diagnostic modalities for managing rare tumors like this.